Implementation of Buying and Selling Transactions in the Perspective of Islamic Economics : (Case Study of Traders at the Kauman People's Market, Tulungagung) - Mei Santi; Misbakhul Khaer; Wahyu Firmansyah (EKSYAR : Jurnal Ekonomi Syari'ah & Bisnis Islam (e-Journal), 2023)
Trade is an economic activity that must be connected to the role of today's society in meeting their daily needs. This trading activity is marked by an agreement or agreement between two parties, namely between the trader and the buyer. In this study, the researcher wants to conduct research in the Pasar Rakyat Kauman Tulungagung with the formulation of the problem, namely how to implement the buying and selling transactions of traders in the Pasar Rakyat Kauman Tulungagung from a conventional perspective and an Islamic economic perspective. In this study, researchers used qualitative research methods. The data sources used by researchers are primary data and secondary data. Then the data collection techniques that researchers use are general interviews, passive participation observation, and documentation. The data analysis technique that the researcher uses is data reduction, while to check the data's validity, the researcher uses the observation extension technique. The results of this study indicate that buying and selling transactions carried out by traders at the Pasar Rakyat Kauman Tulungagung are under the perspective of Islamic economics, that they are also correlated with the Kitab Undang-Undang Hukum Perdata on Ketentuan-ketentuan Umum tentang Jual Beli issued by Jaringan Dokumentasi dan Informasi Hukum (JDIH) in Article 1457.